Ketepatan Pemeriksaan Imunohistokimia CK19 Dibandingkan dengan PDX-1 pada Tumor Pankreas dan Anak Sebarnya - Nur Rahadiani; Bayu Perkasa Rosari; Michelle Linggodigdo; Yan Cahya Wijaya; Marini Stephanie (Majalah Patologi Indonesia, 2021)
BackgroundMetastatic adenocarcinoma of unknown origin remains a serious problem in oncology. Pancreatic cancer is often diagnosed when ithas already metastasized. Therefore immunohistochemistry (IHC) examination for detecting metastases of pancreatic origin is veryimportant IHC marker of Pancreatic duodenal homeobox-1 (PDX-1) has a good accuracy for detecting metastases of pancreaticorigin, however it is not readily available in many centers in Indonesia. Instead, IHC marker that is often being used is CK19. Thismarker is not specific, because it is also expressed by gastrointestinal and hepatobilliary tumors. This evidence-based case reportaims to determine the accuracy of CK19 compared with PDX-1 IHC for detecting pancreatic tumor and its metastases.MethodsLiterature searches were conducted on Pubmed/MEDLINE®, Scopus®, Cochrane®databases. Four articles about PDX-1 and 5 articlesabout CK19 that are relevant were found. Those articles were critically appraised.ResultsAll articles are considered valid, as they fulfilled the important criteria for journal validity. A study of CK19 IHC found that this markerhas 100% sensitivity and 6% specificity for diagnosing liver metastases from well-differentiated pancreatic ductal adenocarcinoma.Studies of PDX-1 IHC have different results; a study found that 27 out of 67 were PDX-1 positive in metastases of pancreaticadenocarcinoma origin, while another study found that PDX-1 has 72% sensitivity and 93% specificity for pancreatic neuroendocrinetumor, with 100% sensitivity and 75% specificity for pancreatic neuroendocrine tumor metastases.ConclusionCK19 IHC is highly sensitive for detecting adenocarcinoma metastases of pancreatic origin, thus it can be utilized as a screening test.However, CK19 IHC specificity for detecting adenocarcinoma metastases of pancreatic origin is low compared to PDX-1 IHC